Nutritional support in sports: Part I. The role of macronutrients in increasing of endurance of athletes (review of foreign literature) - M. M. Korosteleva; I. V. Kobel'kova; R. A. Khanferyan (National Electronic Information Consortium (NEICON), 2020)
A balanced diet and intake of Specialized foodstuffs products play a key role in expanding the adaptive potential of athletes and affect the effectiveness of the training process. The review examines the current scientific evidence regarding the nutritional and energy needs of athletes to increase endurance. Comparative characteristics of various sources of protein, carbohydrates are given, the value of fats in sports practice, as well as the effectiveness of the use of combinations of various macronutrients during intense physical exertion are characterized.